text thresholds in Abdel-Amir Khalil's group "Makadat Al-Hafi" as an applied model. (Journal of the College of Basic Education, 2023)
Summary of the research:Textual thresholds are among the most important topics dealt with by semiotics in study and analysis. They are external and internal appendices of the text and serve as a preliminary idea that puts the reader into the general atmosphere of the text. Therefore, it is a necessary station that requires the reader to go through it to stand on the merits of the text and reveal the author’s intentions behind those texts. Thus, it serves as a sign indicating the decipherment of the text, extrapolation and removal of ambiguity from it, and we have chosen Abdel-Amir Khalil's group "Makadat Al-Hafi" as an applied model for this study, so we concluded that each text has a threshold to be divided into: the title, the author, the panels "external and internal" and the dedication, ....Keywords: threshold - platform, title - cover - sexual indicator threshold